Washable self-adaptive temperature-adjusting fabric and preparation method thereof
By using silica shell coated with phase-change paraffin and n-octadecane materials, phase-change microcapsules with high packaging rate and high enthalpy value are formed, and textile them into water-resistant adaptive temperature-regulating fabrics, which solves the problems of low thermal conductivity and poor stability of shell materials in the prior art, and achieves efficient temperature adjustment and water-resistant effects.
Patent Information
- Application Number
- CN202510277056.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-06-10
AI Technical Summary
In the prior art, organic shell materials commonly used to coat phase change materials have problems such as low thermal conductivity, poor stability and formaldehyde emission, which are difficult to meet the needs of efficient temperature adjustment and water washing resistance.
Silica is used as the shell material, and SiO2 shell is formed under water bath ultrasonic treatment through sodium silicate as the precursor, and phase change materials such as phase change paraffin and n-octadecane are coated to form phase change microcapsules with high encapsulation rate and high enthalpy value, and they are woven into water-resistant adaptive temperature-regulating fabrics.
The packaging rate and melting enthalpy of phase change microcapsules are improved, the utilization rate and temperature adjustment performance of phase change materials are enhanced, the washing resistance of fabrics is improved, and the thermal stability and protection effect of phase change materials are improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fabrics, and more specifically, to a water-washable self-adaptive temperature-regulating fabric and a preparation method thereof. Background Art
[0002] Fabrics are materials used to make clothing; common clothing fabrics mainly include cotton, linen, silk, leather, chemical fiber, blended, modal, etc.; in order to meet people's requirements for the comfort and functionality of textiles, the combination of phase change microcapsules and textiles to prepare heat storage and temperature-regulating textiles has become a current research hotspot; phase change temperature-regulating fabrics can respond to heat and cold stimuli with corresponding temperature increases or decreases without relying on external induction and reaction equipment, and have the functions of automatically absorbing, storing, distributing, and releasing heat, and can achieve two-way intelligent temperature regulation within a certain range; temperature-regulating fibers are coated with thermosensitive phase change materials through microcapsule technology and implanted inside the fibers, so that the fiber materials have the function of absorbing, storing, and releasing heat in the form of latent heat.
[0003] Common shell materials for coating phase change materials include organic materials such as polyurea, polystyrene, and melamine resin, but organic shell materials have problems such as low thermal conductivity, poor stability, and formaldehyde release. Compared with organic shell materials, inorganic shell materials have higher thermal conductivity and better mechanical properties, mainly including silica, titanium dioxide, and calcium carbonate, among which silica has attracted much attention due to its non-toxicity, stable structure, and strong thermal conductivity. Summary of the Invention
[0004] In order to overcome the above-mentioned defects of the prior art, an embodiment of the present invention provides a water-washable self-adaptive temperature-regulating fabric and a preparation method thereof.
[0005] A water-washable self-adaptive temperature-regulating fabric is obtained by spinning and weaving phase change fibers to obtain the water-washable self-adaptive temperature-regulating fabric; the raw materials of the phase change fibers include, calculated by weight percentage: 6.8-7.1% of polyacrylonitrile powder, 0.42-0.50% of phase change microcapsules, and the rest is dimethylformamide.
[0006] Further, the raw materials of the phase change microcapsules include, calculated by weight percentage: 18.50-18.90% of phase change paraffin, 24.80-25.80% of emulsifier, 13.85-14.15% of polyvinylpyrrolidone, 4.90-5.10% of sodium silicate, and the rest is n-octadecane.
[0007] Further, the emulsifier includes cetyltrimethylammonium bromide and sodium dodecyl sulfate, and the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:11-13.
[0008] Further, the phase change fiber raw materials by weight percentage include: 6.9 - 7.0% of polyacrylonitrile powder, 0.16 - 0.19% of azobisisobutyronitrile, 0.45 - 0.47% of phase change microcapsules, and the balance is dimethylformamide; the phase change microcapsule raw materials by weight percentage include: 18.60 - 18.80% of phase change paraffin, 25.10 - 25.50% of emulsifier, 13.95 - 14.05% of polyvinylpyrrolidone, 4.95 - 5.05% of sodium silicate, and the balance is n-octadecane; the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:11.5 - 12.5.
[0009] Further, the phase change fiber raw materials by weight percentage include: 6.95% of polyacrylonitrile powder, 0.18% of azobisisobutyronitrile, 0.46% of phase change microcapsules, and the balance is dimethylformamide; the phase change microcapsule raw materials by weight percentage include: 18.70% of phase change paraffin, 25.30% of emulsifier, 14.00% of polyvinylpyrrolidone, 5.00% of sodium silicate, and the balance is n-octadecane; the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:12.
[0010] A preparation method of a water-washable self-adaptive temperature-regulating fabric is as follows:
[0011] Step 1: Weigh polyacrylonitrile powder, dimethylformamide, phase change paraffin, polyvinylpyrrolidone, sodium silicate, n-octadecane, cetyltrimethylammonium bromide and sodium dodecyl sulfate.
[0012] Step 2: Add phase change paraffin, polyvinylpyrrolidone, n-octadecane, cetyltrimethylammonium bromide and sodium dodecyl sulfate into an ethanol solution, perform water bath stirring for 20 - 40 minutes, then carry out high-speed emulsification and ultrasonic treatment for 10 - 20 minutes to obtain a homogeneous emulsion.
[0013] Step 3: Add sodium silicate into deionized water, perform water bath ultrasonic treatment for 20 - 40 minutes to obtain a sodium silicate solution, adjust the pH = 3.0 - 4.0 to obtain a silica precursor solution.
[0014] Step 4: Under water bath stirring, drop the silica precursor solution into the homogeneous emulsion. After the dropping is completed, adjust the pH = 6.0 - 7.0 after 1 hour, and continue to react for 18 - 24 hours under water bath conditions, then centrifuge, wash and dry to obtain phase change microcapsules.
[0015] Step 5: Add the phase change microcapsules and polyacrylonitrile powder into dimethylformamide, stir for 20 - 40 minutes to obtain a spinning solution. The spinning solution is extruded through a spinneret hole, solidified and formed in a coagulation bath, drawn in the coagulation bath, washed with water, hot water drawn, oiled, dried and densified, thermally relaxed, steam high-pressure drawn, and heat-set to obtain phase change fibers; the phase change fibers are spun and woven to obtain a water-washable self-adaptive temperature-regulating fabric.
[0016] Further, in Step 2, the water bath temperature is 65 - 75 °C, the stirring speed is 600 - 800 r / min, the emulsifying speed is 7800 - 8200 r / min, the ultrasonic treatment frequency is 1.2 - 1.4 MHZ, the ultrasonic power is 400 - 500 W, the weight ratio of n-octadecane to ethanol solution is 1:35 - 40, and the concentration of the ethanol solution is 75%; in Step 3, the ultrasonic treatment frequency is 1.2 - 1.4 MHZ, the ultrasonic power is 400 - 500 W, the water bath temperature is 65 - 75 °C, the pH value is adjusted using a hydrochloric acid solution, and the weight ratio of sodium silicate to deionized water is 1:150 - 200.
[0017] Further, in Step 4, the water bath temperature is 55 - 65 °C, the stirring speed is 300 - 500 r / min, the pH value is adjusted using ammonia water, and the centrifugation speed is 2800 - 3200 r / min.
[0018] Further, in Step 5, the spinning process is as follows: The spinning solution is extruded through a spinneret to form a fine stream, enters the first coagulation bath of coagulation liquid I through an air layer, and then enters the second coagulation bath of coagulation liquid II; the temperature of the first coagulation bath is 43 - 47 °C, and the temperature of the second coagulation bath is 27 - 29 °C; the spinning solution is metered by a metering pump and extruded through a spinneret with a pore diameter of 0.05 - 0.08 mm to form a fine stream, and the thickness of the air layer is 22 - 25 mm; coagulation bath drawing, water washing, hot water drawing, oiling: First, pre-stretch the coagulated fibers obtained after the second coagulation bath 1.2 - 1.5 times in a water bath at 78 - 82 °C, then wash with water at 73 - 77 °C, and then treat in an amino silicone oil emulsion to obtain oiled fibers; drying and densification, thermal relaxation, steam high-pressure drawing, heat setting: Perform drying and densification treatment at 165 - 175 °C, perform thermal relaxation treatment through a hot air box, perform steam high-temperature high-pressure high-magnification drawing treatment, and heat setting to obtain phase change fibers; the time for drying and densification treatment is 40 - 50 s, the temperature for thermal relaxation treatment is 103 - 107 °C, the time is 10 - 20 s, the saturated steam pressure for steam high-temperature high-pressure high-magnification drawing treatment is 0.12 - 0.18 MPa, the drawing ratio is 2 - 5 times, and the temperature for heat setting is 350 - 360 °C, and the time is 2 - 3 minutes.
[0019] Further, in Step 2, the water bath temperature is 70°C, the stirring speed is 700 r / min, the emulsification speed is 8000 r / min, the ultrasonic treatment frequency is 1.3 MHz, the ultrasonic power is 450 W, and the weight ratio of n-octadecane to ethanol solution is 1:37.5; in Step 3, the ultrasonic treatment frequency is 1.3 MHz, the ultrasonic power is 450 W, the water bath temperature is 70°C, the pH value is adjusted using a hydrochloric acid solution, and the weight ratio of sodium silicate to deionized water is 1:175; in Step 4, the water bath temperature is 60°C, the stirring speed is 400 r / min, the pH value is adjusted using ammonia water, and the centrifugation speed is 3000 r / min; in Step 5, the spinning process is as follows: the spinning solution is extruded through a spinneret to form a fine stream, enters the first coagulation bath of coagulation liquid I through an air layer, and then enters the second coagulation bath of coagulation liquid II; the temperature of the first coagulation bath is 45°C, and the temperature of the second coagulation bath is 28°C; the spinning solution is metered by a metering pump and extruded through a spinneret with a pore diameter of 0.06 mm to form a fine stream, and the thickness of the air layer is 23 mm; coagulation bath drawing, water washing, hot water drawing, and oiling: first, the coagulated fiber obtained after the second coagulation bath is pre-stretched 1.4 times in an 80°C water bath, then washed with 75°C water, and then treated in an amino silicone oil emulsion to obtain an oiled fiber; drying densification, heat relaxation, high-pressure steam drawing, and heat setting: drying densification treatment is carried out at 170°C, heat relaxation treatment is carried out through a hot air box, high-pressure high-temperature high-magnification steam drawing treatment, and heat setting can obtain phase change fibers; the time for drying densification treatment is 45 s, the temperature for heat relaxation treatment is 105°C, the time is 15 s, the saturated steam pressure for high-pressure high-temperature high-magnification steam drawing treatment is 0.15 MPa, the drawing ratio is 4 times, and the temperature for heat setting is 355°C, and the time is 3 minutes.
[0020] Technical effects and advantages of the present invention:
[0021] 1. The washable self-adaptive temperature-regulating fabric prepared using the raw material formula of the present invention can effectively improve the encapsulation rate and melting enthalpy of phase change microcapsules in the self-adaptive temperature-regulating fabric, thereby effectively improving the utilization rate and temperature-regulating performance of the phase change material, further effectively improving the temperature-regulating performance of the self-adaptive temperature-regulating fabric, and at the same time improving the washability of the self-adaptive temperature-regulating fabric; under the action of cationic cetyltrimethylammonium bromide (CTAB), the silica precursor is anchored on the surface of the phase change material (phase change paraffin and n-octadecane) micelles through hydrogen bond / ionic bond interaction; thereafter, the increase in pH promotes the dehydration condensation between the precursor Si—OH, and then SiO 2The shell successfully encapsulates the phase change materials (phase change paraffin and n-octadecane); as the proportion of the phase change materials (phase change paraffin and n-octadecane) increases, more micelles and binding sites of the phase change materials (phase change paraffin and n-octadecane) are formed, reducing the self-condensation ratio of the silica precursor, thus improving the encapsulation rate of the phase change capsules; using sodium silicate as the precursor to prepare SiO 2 shell layer, using the phase change materials (phase change paraffin and n-octadecane) as the core material, a kind of phase change capsule with low cost, high encapsulation rate and high enthalpy value is prepared; SiO 2 The formation of the shell layer improves the thermal stability of the phase change materials (phase change paraffin and n-octadecane); SiO 2 The shell layer provides good protection for the phase change material (phase change paraffin and n-octadecane) core material of the phase change capsule, preventing the leakage of the phase change material (phase change paraffin and n-octadecane) after melting;
[0022] 2. In the present invention, phase change paraffin, polyvinylpyrrolidone, n-octadecane, cetyltrimethylammonium bromide and sodium dodecyl sulfate are added to an ethanol solution, followed by water bath ultrasonic treatment, high-speed emulsification and ultrasonic treatment; through high-speed emulsification, a relatively high shear force is provided for the system, enabling n-octadecane to be dispersed in the aqueous phase in the form of droplets to form a stable emulsion. The emulsifier provides sufficient viscous stress and surface tension for the core material, resulting in agglomeration between the droplets. The core material emulsion has good stability, and the coating of the wall material monomer on the core material can proceed smoothly, ensuring the enthalpy value of the microcapsules; sodium silicate is added to deionized water for water bath ultrasonic treatment and pH adjustment, which can effectively ensure the normal formation of the silica precursor and the subsequent preparation of microcapsules; before the water bath stirring adjustment, the silica precursor solution is dropped into the homogeneous emulsion, and then the pH value is adjusted, which can effectively ensure the dehydration condensation between the precursor Si—OH, and then form, SiO 2 shell, successfully encapsulating the phase change materials (phase change paraffin and n-octadecane); adding the phase change microcapsules and polyacrylonitrile powder into dimethylformamide to make a spinning solution, then carrying out spinning processing to obtain phase change fibers, and then spinning and weaving the phase change fibers to obtain a washable self-adaptive temperature-regulating fabric. Specific embodiments
[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0024] Example 1:
[0025] The present invention provides a water-washable self-adaptive temperature-regulating fabric, which is obtained by spinning and weaving phase-change fibers to obtain the water-washable self-adaptive temperature-regulating fabric; the raw materials of the phase-change fibers include, by weight percentage: 6.8% of polyacrylonitrile powder, 0.42% of phase-change microcapsules, and the rest is dimethylformamide; the raw materials of the phase-change microcapsules include, by weight percentage: 18.50% of phase-change paraffin, 24.80% of emulsifier, 13.85% of polyvinylpyrrolidone, 4.90% of sodium silicate, and the rest is n-octadecane; the emulsifier includes cetyltrimethylammonium bromide and sodium dodecyl sulfate, and the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:11;
[0026] A preparation method of the water-washable self-adaptive temperature-regulating fabric, and the specific preparation steps are as follows:
[0027] Step 1: Weigh polyacrylonitrile powder, dimethylformamide, phase-change paraffin, polyvinylpyrrolidone, sodium silicate, n-octadecane, cetyltrimethylammonium bromide and sodium dodecyl sulfate;
[0028] Step 2: Add phase-change paraffin, polyvinylpyrrolidone, n-octadecane, cetyltrimethylammonium bromide and sodium dodecyl sulfate into an ethanol solution, perform water-bath stirring treatment for 30 minutes, then perform high-speed emulsification and ultrasonic treatment for 15 minutes to obtain a homogeneous emulsion; the water-bath temperature is 65°C, the stirring speed is 600 r / min, the emulsification speed is 7800 r / min, the ultrasonic treatment frequency is 1.2 MHz, the ultrasonic power is 400 W, the weight ratio of n-octadecane to the ethanol solution is 1:35, and the concentration of the ethanol solution is 75%;
[0029] Step 3: Add sodium silicate into deionized water, perform water-bath ultrasonic treatment for 30 minutes to obtain a sodium silicate solution, adjust the pH = 3.5 to obtain a silicon dioxide precursor solution; the ultrasonic treatment frequency is 1.2 MHz, the ultrasonic power is 400 W, the water-bath temperature is 65°C, use a hydrochloric acid solution to adjust the pH value, and the weight ratio of sodium silicate to deionized water is 1:150;
[0030] Step 4: Under water-bath stirring treatment, drop the silicon dioxide precursor solution into the homogeneous emulsion, adjust the pH = 6.5 1 hour after the dropping is completed, continue to react for 21 hours under water-bath conditions, centrifuge, wash, and dry to obtain phase-change microcapsules; the water-bath temperature is 55°C, the stirring speed is 300 r / min, use ammonia water to adjust the pH value, and the centrifuge speed is 2800 r / min;
[0031] Step 5: Add phase change microcapsules and polyacrylonitrile powder into dimethylformamide, and stir for 20 - 40 minutes to obtain a spinning solution. The spinning process is as follows: Extrude the spinning solution through a spinneret to form a thin stream, enter the first coagulation bath of coagulation liquid I through an air layer, and then enter the second coagulation bath of coagulation liquid II; the temperature of the first coagulation bath is 43 °C, and the temperature of the second coagulation bath is 27 °C; the spinning solution is metered by a metering pump and extruded through a spinneret with a pore diameter of 0.05 mm to form a thin stream, and the thickness of the air layer is 22 mm; Coagulation bath drawing, water washing, hot water drawing, oiling: First, pre - stretch the coagulated fiber obtained after the second coagulation bath 1.2 times in a 78 °C water bath, then wash it with 73 °C water, and then place it in an amino - siloxane emulsion for treatment to obtain an oiled fiber; Drying densification, heat relaxation, high - pressure steam drawing, heat setting: Carry out drying densification treatment at 165 °C, perform heat relaxation treatment through a hot air box, high - pressure high - temperature high - multiple steam drawing treatment, and heat setting to obtain phase - change fibers; The time for drying densification treatment is 40 s, the temperature for heat relaxation treatment is 103 °C, and the time is 10 s. The saturated steam pressure for high - pressure high - temperature high - multiple steam drawing treatment is 0.12 MPa, the drawing ratio is 2 times, and the temperature for heat setting is 350 °C, and the time is 2 minutes; The phase - change fibers are spun and woven to obtain a water - washable self - adaptive temperature - regulating fabric; Coagulation liquid I is an aqueous solution of 1 - butyl - 3 - methylimidazolium chloride with a mass concentration of 30%, and coagulation liquid II is an aqueous solution of dimethyl sulfoxide with a mass concentration of 8%.
[0032] The polyacrylonitrile powder is purchased from Dongguan Shengbang High - Molecular Materials Co., Ltd., with a molecular weight of 50,000; the dimethylformamide is N,N - dimethylformamide purchased from Jinan Chuangshi Chemical Co., Ltd., product number: HG0206; the phase - change paraffin is purchased from Dongguan Shengbang High - Molecular Materials Co., Ltd.; the polyvinylpyrrolidone is purchased from Nantong Runfeng Petrochemical Co., Ltd., product number: R173; the sodium silicate is purchased from Nantong Runfeng Petrochemical Co., Ltd.; the n - octadecane is purchased from Shanghai Yuanye Bio - Technology Co., Ltd., product number: S48787; the cetyltrimethylammonium bromide is purchased from Shanghai Yuanye Bio - Technology Co., Ltd., product number: S15001; the sodium dodecyl sulfate is purchased from Shanghai Yuanye Bio - Technology Co., Ltd., product number: S15012.
[0033] Example 2:
[0034] Different from Example 1, the phase change fiber raw materials include, by weight percentage: 7.1% polyacrylonitrile powder, 0.50% phase change microcapsules, and the rest is dimethylformamide; the phase change microcapsule raw materials include, by weight percentage: 18.90% phase change paraffin, 25.80% emulsifier, 14.15% polyvinylpyrrolidone, 5.10% sodium silicate, and the rest is n-octadecane; the emulsifier includes cetyltrimethylammonium bromide and sodium dodecyl sulfate, and the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:13.
[0035] Example 3:
[0036] Different from both Example 1 and Example 2, the phase change fiber raw materials include, by weight percentage: 6.95% polyacrylonitrile powder, 0.46% phase change microcapsules, and the rest is dimethylformamide; the phase change microcapsule raw materials include, by weight percentage: 18.70% phase change paraffin, 25.30% emulsifier, 14.00% polyvinylpyrrolidone, 5.00% sodium silicate, and the rest is n-octadecane; the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:12.
[0037] Example 4:
[0038] Different from Example 3, in Step 2, the water bath temperature is 70°C, the stirring speed is 700 r / min, the emulsifying speed is 8000 r / min, the ultrasonic treatment frequency is 1.3 MHz, the ultrasonic power is 450 W, and the weight ratio of n-octadecane to ethanol solution is 1:37.5; in Step 3, the ultrasonic treatment frequency is 1.3 MHz, the ultrasonic power is 450 W, the water bath temperature is 70°C, the pH value is adjusted using hydrochloric acid solution, and the weight ratio of sodium silicate to deionized water is 1:175; in Step 4, the water bath temperature is 60°C, the stirring speed is 400 r / min, the pH value is adjusted using ammonia water, and the centrifugation speed is 3000 r / min; in Step 5, the spinning process is as follows: the spinning solution is extruded through a spinneret to form a fine stream, enters the first coagulation bath of coagulation liquid I through an air layer, and then enters the second coagulation bath of coagulation liquid II; the temperature of the first coagulation bath is 45°C, and the temperature of the second coagulation bath is 28°C; the spinning solution is metered by a metering pump and extruded through a spinneret with a pore diameter of 0.06 mm to form a fine stream, and the thickness of the air layer is 23 mm; coagulation bath drawing, water washing, hot water drawing, oiling: first pre-stretch the coagulated fiber obtained after the second coagulation bath 1.4 times in an 80°C water bath, then wash it with 75°C water, and then treat it in an amino silicone emulsion to obtain an oiled fiber; drying densification, heat relaxation, steam high-pressure drawing, heat setting: perform drying densification treatment at 170°C, perform heat relaxation treatment through a hot air box, perform steam high-temperature high-pressure high-ratio drawing treatment, and heat setting to obtain phase change fibers; the time for drying densification treatment is 45 s, the temperature for heat relaxation treatment is 105°C, the time is 15 s, the saturated steam pressure for steam high-temperature high-pressure high-ratio drawing treatment is 0.15 MPa, the drawing ratio is 4 times, and the temperature for heat setting is 355°C, and the time is 3 minutes.
[0039] Comparative Example 1:
[0040] Different from Example 4: The phase change fiber raw materials include, by weight percentage: 6.95% polyacrylonitrile powder, 0.46% phase change microcapsules, and the rest is dimethylformamide; the phase change microcapsule raw materials include, by weight percentage: 18.70% phase change paraffin, 25.30% emulsifier, 14.00% polyvinylpyrrolidone, 5.00% tetraethyl orthosilicate, and the rest is n-octadecane; the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:12.
[0041] Comparative Example 2:
[0042] Different from Example 4, the phase change fiber raw material comprises, by weight percentage: 6.95% of polyacrylonitrile powder, 0.46% of phase change microcapsules, and the balance is dimethylformamide; the phase change microcapsule raw material comprises, by weight percentage: 18.70% of phase change paraffin, 25.30% of emulsifier, 14.00% of polyvinylpyrrolidone, 5.00% of tetraethoxysilane, and the balance is n-octadecane; the weight ratio of cetyltrimethylammonium bromide to sodium dodecyl sulfate is 1:12.
[0043] The water-washable self-adaptive temperature-regulating fabrics in the comparative examples and examples of the present invention were subjected to detection and treatment:
[0044] A differential scanning calorimeter (DSC, DSC 200PC type, manufactured by NETZSCH, Germany) was used to measure the phase change performance of the material; Er); Er = ΔHm,PSΔHm,PCM;
[0045] ΔHm,PS is the melting enthalpy value of the phase change capsule, J / g; ΔHm,PCM is the melting enthalpy value of the phase change material (phase change paraffin and n-octadecane), J / g;
[0046] The results are shown in Table 1:
[0047] Table 1:
[0048]
[0049] As can be seen from the above table, the water-washable self-adaptive temperature-regulating fabric of the present invention can effectively improve the encapsulation rate and melting enthalpy of the phase change microcapsules in the self-adaptive temperature-regulating fabric, thereby effectively improving the utilization rate and temperature-regulating performance of the phase change material, further effectively improving the temperature-regulating performance of the self-adaptive temperature-regulating fabric, and at the same time improving the water-washable performance of the self-adaptive temperature-regulating fabric.
[0050] In the present invention, sodium silicate is uniformly dispersed in deionized water under heating and adjusted to be acidic to obtain a silica precursor. Under the action of the cationic cetyltrimethylammonium bromide (CTAB), the silica precursor is anchored on the surface of the micelles of the phase change material (phase change paraffin and n-octadecane) through hydrogen bond / ionic bond interaction; thereafter, the increase in pH promotes the dehydration condensation between the precursor Si—OH, and then SiO 2 shell is formed to successfully coat the phase change material (phase change paraffin and n-octadecane); with the increase in the proportion of the phase change material (phase change paraffin and n-octadecane), more micelles and binding sites of the phase change material (phase change paraffin and n-octadecane) are formed, reducing the self-condensation ratio of the silica precursor, so the encapsulation rate of the phase change capsule is increased; using sodium silicate as the precursor to prepare SiO 2A shell layer was used with phase change materials (phase change paraffin and n-octadecane) as the core material to prepare a phase change capsule with low cost, high encapsulation rate, and high enthalpy value. There was no chemical reaction between the core of the phase change materials (phase change paraffin and n-octadecane) and the SiO 2 shell, and the SiO 2 coating did not change the phase change behavior of the core material of the phase change materials (phase change paraffin and n-octadecane). The phase change capsules were mainly distributed at the sub-micron level. A smaller particle size means a larger specific surface area, and the increase in the specific surface area enhances the heat transfer area of the phase change materials (phase change paraffin and n-octadecane), thereby endowing the phase change capsules with high heat storage and heat release efficiency. The SiO 2 shell does not have the ability to undergo phase change. Therefore, the larger the proportion of the core material, the higher the enthalpy value of the phase change capsule. The formation of the SiO 2 shell layer improves the thermal stability of the phase change materials (phase change paraffin and n-octadecane). The SiO 2 shell layer provides good protection for the core material of the phase change materials (phase change paraffin and n-octadecane) of the phase change capsule, preventing the leakage of the phase change materials (phase change paraffin and n-octadecane) after melting. During the heating process, the phase change capsules start to store heat when approaching the phase change temperature, and start to release heat when approaching the crystallization temperature during the cooling process. Therefore, there are "platforms" for heat storage and heat release on the temperature-time curve, which also indicates that the phase change capsules have good heat regulation ability;
[0051] In step two, phase change paraffin, polyvinylpyrrolidone, n-octadecane, cetyltrimethylammonium bromide, and sodium dodecyl sulfate were added to an ethanol solution, followed by water bath ultrasonic treatment, high-speed emulsification, and ultrasonic treatment. Through high-speed emulsification, a higher shear force was provided to the system, enabling n-octadecane to be dispersed in the aqueous phase in the form of droplets to form a stable emulsion. The emulsifier provided sufficient viscous stress and surface tension for the core material, resulting in agglomeration between the droplets. The core material emulsion had good stability, and the coating of the wall material monomer on the core material could proceed smoothly, ensuring the enthalpy value of the microcapsules. In step three, sodium silicate was added to deionized water for water bath ultrasonic treatment and pH adjustment, which could effectively ensure the normal formation of the silica precursor and the subsequent preparation of microcapsules. In step four, before water bath stirring and adjustment, the silica precursor solution was dropped into the homogeneous emulsion, and then the pH value was adjusted, which could effectively ensure the dehydration condensation between the precursor Si—OH, and then form the SiO 2 shell, successfully coating the phase change materials (phase change paraffin and n-octadecane). In step five, the phase change microcapsules and polyacrylonitrile powder were added to dimethylformamide to make a spinning solution, and then spinning processing was carried out to obtain phase change fibers. Then the phase change fibers were spun and woven to obtain a washable self-adaptive temperature-regulating fabric.
[0052] Finally, it should be noted that the above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or perform equivalent replacements for some of the technical features. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A washable, self-adaptive, temperature-regulating fabric, characterized in that: The phase change fiber is spun and woven to obtain a washable self-adaptive temperature regulating fabric; the phase change fiber raw material comprises, by weight percentage, 6.8-7.1% of polyacrylonitrile powder, 0.42-0.50% of phase change microcapsules, and the rest is dimethylformamide.
2. The washable adaptive temperature regulating fabric according to claim 1, characterized in that: The phase change microcapsule raw materials include, by weight percentage, 18.50-18.90% of phase change paraffin, 24.80-25.80% of emulsifier, 13.85-14.15% of polyvinyl pyrrolidone, 4.90-5.10% of sodium silicate, and the rest is n-octadecane.
3. The washable self-adaptive temperature regulating fabric according to claim 2, characterized in that: The emulsifier comprises hexadecyltrimethylammonium bromide and sodium dodecyl sulfate, and the weight ratio of the hexadecyltrimethylammonium bromide to the sodium dodecyl sulfate is 1:11-13.
4. The washable self-adaptive temperature regulating fabric according to claim 3, characterized in that: The phase change fiber raw material includes, by weight percentage, 6.9-7.0% of polyacrylonitrile powder, 0.16-0.19% of azobisisobutyronitrile, 0.45-0.47% of phase change microcapsules, and the rest is dimethylformamide; the phase change microcapsule raw material includes, by weight percentage, 18.60-18.80% of phase change paraffin, 25.10-25.50% of emulsifier, 13.95-14.05% of polyvinyl pyrrolidone, 4.95-5.05% of sodium silicate, and the rest is n-octadecane; the weight ratio of hexadecyltrimethylammonium bromide to sodium dodecyl sulfate is 1:11.5-12.
5.
5. The washable self-adaptive temperature regulating fabric according to claim 3, characterized in that: The phase change fiber raw material includes, by weight percentage, 6.95% of polyacrylonitrile powder, 0.18% of azobisisobutyronitrile, 0.46% of phase change microcapsules, and the rest is dimethylformamide; the phase change microcapsule raw material includes, by weight percentage, 18.70% of phase change paraffin, 25.30% of emulsifier, 14.00% of polyvinyl pyrrolidone, 5.00% of sodium silicate, and the rest is n-octadecane; the weight ratio of hexadecyltrimethylammonium bromide to sodium dodecyl sulfate is 1:
12.
6. A method for preparing a washable, self-adaptive, temperature-regulating fabric, characterized in that: The specific preparation steps are as follows: Step 1: Weigh polyacrylonitrile powder, dimethylformamide, phase change paraffin, polyvinyl pyrrolidone, sodium silicate, n-octadecane, hexadecyltrimethylammonium bromide and sodium dodecyl sulfate; Step 2: adding phase change paraffin, polyvinyl pyrrolidone, n-octadecane, hexadecyl trimethyl ammonium bromide and sodium dodecyl sulfate to an ethanol solution, stirring in a water bath for 20 to 40 minutes, and then performing high-speed emulsification and ultrasonic treatment for 10 to 20 minutes to obtain a homogeneous emulsion; Step 3: adding sodium silicate to deionized water, performing water bath ultrasonic treatment for 20 to 40 minutes to obtain a sodium silicate solution, adjusting the pH to 3.0 to 4.0, and obtaining a silicon dioxide precursor solution; Step 4: under stirring in a water bath, the silica precursor solution is added dropwise to the homogeneous emulsion, and the pH is adjusted to 6.0-7.0 1 hour after the addition is completed, and the reaction is continued for 18-24 hours under water bath conditions, and then centrifuged, washed, and dried to obtain phase change microcapsules; Step 5: adding phase change microcapsules and polyacrylonitrile powder into dimethylformamide, stirring for 20 to 40 minutes to obtain a spinning solution, extruding the spinning solution through a spinneret, coagulating and forming in a coagulation bath, drawing in a coagulation bath, washing, drawing in hot water, oiling, drying and densification, heat relaxation, steam high-pressure drawing, and heat setting to obtain phase change fibers; the phase change fibers are spun and woven to obtain washable and self-adaptive temperature-regulating fabrics.
7. The method for preparing a washable adaptive temperature regulating fabric according to claim 6, characterized in that: In step 2, the water bath temperature is 65-75° C., the stirring speed is 600-800 r / min, the emulsification speed is 7800-8200 r / min, the ultrasonic treatment frequency is 1.2-1.4 MHZ, the ultrasonic power is 400-500 W, the weight ratio of n-octadecane to the ethanol solution is 1:35-40, and the concentration of the ethanol solution is 75%; in step 3, the ultrasonic treatment frequency is 1.2-1.4 MHZ, the ultrasonic power is 400-500 W, the water bath temperature is 65-75° C., the pH value is adjusted using a hydrochloric acid solution, and the weight ratio of sodium silicate to deionized water is 1:150-200.
8. The method for preparing a washable adaptive temperature regulating fabric according to claim 7, characterized in that: In step 4, the water bath temperature is 55-65° C., the stirring speed is 300-500 r / min, ammonia water is used to adjust the pH value, and the centrifugal speed is 2800-3200 r / min.
9. The method for preparing a washable adaptive temperature regulating fabric according to claim 8, characterized in that: In step 5, the spinning process is as follows: the spinning solution is extruded through a spinneret to form a thin stream, and enters the coagulation solution I through an air layer for the first coagulation bath, and then enters the coagulation solution II for the second coagulation bath; the temperature of the first coagulation bath is 43-47°C, and the temperature of the second coagulation bath is 27-29°C; the spinning solution is metered by a metering pump and extruded through a spinneret with an aperture of 0.05-0.08 mm to form a thin stream, and the thickness of the air layer is 22-25 mm; coagulation bath drawing, water washing, hot water drawing, and oiling: the coagulated fiber obtained after the second coagulation bath is first pre-stretched 1.2-1.5 times in a 78-82°C water bath, and then washed with 73-77°C water , and then placed in an aminosilicone emulsion for treatment to obtain oiled fiber; drying densification, heat relaxation, steam high-pressure drawing, heat setting: drying densification treatment is carried out at 165-175°C, heat relaxation treatment is carried out through a hot air box, steam high-temperature, high-pressure and high-multiple drawing treatment, and heat setting can obtain phase change fiber; the drying densification treatment time is 40-50s, the heat relaxation treatment temperature is 103-107°C, the time is 10-20s, the saturated water vapor pressure of steam high-temperature, high-pressure and high-multiple drawing treatment is 0.12-0.18MPa, the drawing ratio is 2-5 times, the heat setting temperature is 350-360°C, and the time is 2-3 minutes.
10. The method for preparing a washable adaptive temperature regulating fabric according to claim 9, characterized in that: In step 2, the water bath temperature is 70°C, the stirring speed is 700r / min, the emulsification speed is 8000r / min, the ultrasonic treatment frequency is 1.3MHZ, the ultrasonic power is 450W, and the weight ratio of n-octadecane to ethanol solution is 1:37.5; in step 3, the ultrasonic treatment frequency is 1.3MHZ, the ultrasonic power is 450W, the water bath temperature is 70°C, the pH value is adjusted with hydrochloric acid solution, and the weight ratio of sodium silicate to deionized water is 1:175; in step 4, the water bath temperature is 60°C, the stirring speed is 400r / min, the pH value is adjusted with ammonia water, and the centrifugal speed is 3000r / min; in step 5, the spinning process is as follows: the spinning solution is extruded through a spinneret to form a thin stream, passes through an air layer into coagulation liquid I for the first coagulation bath, and then enters coagulation liquid II for the second coagulation bath; the temperature of the first coagulation bath is 45°C, and the second coagulation The bath temperature is 28°C; the spinning solution is measured by a metering pump and extruded through a spinneret with an aperture of 0.06mm to form a thin flow, and the thickness of the air layer is 23mm; coagulation bath stretching, water washing, hot water stretching, and oiling: the coagulated fiber obtained after the second coagulation bath is first pre-stretched 1.4 times in an 80°C water bath, then washed with 75°C water, and then placed in an aminosilicone emulsion for treatment to obtain oiled fiber; drying densification, heat relaxation, steam high-pressure stretching, and heat setting: drying and densification treatment is carried out at 170°C, heat relaxation treatment is carried out through a hot air box, steam high-temperature and high-pressure high-multiple stretching treatment is carried out, and heat setting can obtain phase change fiber; the drying and densification treatment time is 45s, the heat relaxation treatment temperature is 105°C, the time is 15s, the saturated water vapor pressure of steam high-temperature and high-pressure high-multiple stretching treatment is 0.15MPa, the stretching ratio is 4 times, the heat setting temperature is 355°C, and the time is 3 minutes.